Control and freedom power and paranoia in the age of fiber optics - Chun, Wendy Hui Kyong, 1969- (MIT Press, 2006)
"Drawing on the theories of Gilles Deleuze and Michel Foucault and analyzing such phenomena as Webcams and face-recognition technology, Chun argues that the relationship between control and freedom in networked contact is experienced and negotiated through sexuality and race. She traces the desire for cyberspace to cyberpunk fiction and maps the transformation of public/private into open/closed. Analyzing "pornocracy," she contends that it was through cyberporn and the government's attempts to regulate it that the Internet became a marketplace of ideas and commodities.